Rural 'Italies' and the Great Crisis. Provincial clusters in Italian agriculture between the two world wars. Issue 5 (20th October 2018) - Chiapparino, Francesco; Morettini, Gabriele
ABSTRACT: This article aims to investigate the dynamics of Italian agriculture during the crisis of the 1930s, as well as related issues such as the role of some policies deployed to contain the recession and their consequences. To that end, the article adopts a particular viewpoint based on the belief that Italy presents a large variety of rural environments, the result of its geography and history, and is characterized by different cultivations, features, conduction systems, productivity levels, and market orientations – in other words, diverse modes of production. Partitioning these 'rural Italies' allows us to analyse their trends and prevents them from being bundled together in such a way as to compensate and sometimes even nullify each other. Moreover, the Fascist regime introduced active incentive and protectionist (even autarkic) policies to contrast the recession. Split into the plurality of its agrarian contexts, therefore, the country becomes a sort of kaleidoscope, through which it is possible to observe both the relatively wide set of effective changes brought about by the depression and the diverse impact of national policies.